Clinical Pharmacological Approach To The Drug Treatment Of Arthritis, Arthralgia And Back Pain Syndromes (Texas Journal of Medical Science, 2025)
The article is devoted to one of the most common rheumatic diseases — juvenile arthritis (JA). The main issues of epidemiology, classification, pathogenesis are considered, in more detail — the clinical picture of different variants of the course of JA, diagnostics and differential diagnosis. The treatment section describes the drugs used in JA, and presents an algorithm for differentiated treatment of the disease. Approaches to biological therapy, conditions for prescribing and management of patients receiving genetically engineered biological drugs are described separately.